تقنيات الحوار في تدريس اللغة العربية سنة ثانية متوسط أنموذجا - داده, غربي, مريم فاطمة الزهراء; بوصبيع ابراهيم, يسرى (University of El-oued, 2022)
تسعى هذه الدراسة للكشف عن مدى نجاعة الطريقة الحوارية التواصلية في بناء عملية تعليمية ناجحة ،ووفق مداخل نظرية وإجراءات منهجية ،مكنتنا من التعرف أكثر على الطريقة الحوارية في عملية التدريس ،لما تشمله من آليات وأساليب تساعد المتعلم على بناء كفاءات متجددة ومتطورة ،وفق أدائه المعرفي والمنهجي . لم يعد التدريس بالطرق الكلاسيكية ناجحا كما هو بالطرق الحديثة التى تعتمد التواصل المباشر مع المتعلم . وهذا الأخير الذي أصبح طرف مباشر ومؤثر في تلك العملية يحاور يناقش ،يتواصل . This study seeks to reveal the extent of the effectiveness of the communicative dialogue method in building a successful educational faculty according to theoretical approaches and method logic prxedures that enabled us to learn more about the dialogue method in the teaching process ,because of the mechanisms and methods that itinchdes that help the learner to build renewable and advanced competencies according to his cognitive and method logical performance . Teaching using the classical method is nalonger as successful as the modern methods that depend on direct communication with the learner. The latter ,who became a direct and influential party in that process ,debates ,discuses ,and communication.
مدارس مختارة
Keywords: الحوار. اللغة العربية . التدريس